Strategi Manajemen Pendidikan Islam Dalam Meningkatkan Disiplin Santri di Pondok Pesantren Modern - Muhammad Rubil (Jaanur Elbarik Indonesia, 2026)
Discipline is one of the key indicators of educational success because it reflects students' compliance with institutional regulations, sense of responsibility, and the implementation of Islamic values in their daily lives. Therefore, effective Islamic educational management strategies are required to optimize the development of student discipline. This study aims to analyze Islamic educational management strategies in improving student discipline at modern Islamic boarding schools. The study employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing techniques. The validity of the data was ensured through triangulation.The findings indicate that Islamic educational management strategies were implemented through the planning of disciplinary programs, the organization of educators' and dormitory supervisors' responsibilities, the continuous implementation of character development through habituation and exemplary behavior, as well as the application of educational rewards and sanctions. In addition, consistent supervision and collaboration among school leaders, teachers, dormitory supervisors, and parents contributed to the establishment of a culture of discipline within the boarding school.